Ação de revestimento comestível a base de amido e de antioxidante na conservação de inhame (Dioscorea spp.) minimamente processado - Furtado, Mateus de Carvalho (2013)
The aim of this study was to evaluate the effect of edible coating of cassava starch associated with the incorporation of ascorbic acid in the conservation of yam (Dioscorea spp.) minimally processed. The minimally processed products were packed in polystyrene trays and wrapped in film polyvinylchloride (PVC). The yams were stored for 12 days at 8 ± 1°C and subjected to different treatments: control (T1); coated (T2); with 1% ascorbic acid (T3); coating and 1% ascorbic acid (T4); coating 1% ascorbic acid and 1% citric acid (T5). We evaluated the physicochemical changes (weight loss, browning index, maximum compression, total soluble solids, pH and acidity), biochemical changes (total phenols and polyphenol oxidase activity) and physiological responses (CO2 concentration, ethylene concentration, respiration rate and ethylene evolution). The products of the treatments with edible coating had lower mass loss at the end of storage, however the five treatments reached values near and below 2%. Regarding the analysis of maximum compression, soluble solids, pH and acidity, the five treatments studied showed no significant effects. Treatment with 1% ascorbic acid (T3) had the lowest browning index and was efficient in control of biochemical factors, obtaining the highest total phenolic content and the lowest values of the activity of the enzyme polyphenol oxidase during the 12 days of storage. Regarding physiological analyzes, it was found that the edible coating was effective in slowing the respiratory metabolism and ascorbic acid influenced the respiratory system of yams. We did not detect the presence of ethylene, indicating a low production of this gas in minimally processed yam. The treatment with 1% ascorbic acid (T3), associated with the appropriate minimum processing and control of storage conditions (temperature and humidity), was effective in the conservation of minimally processed yam. Since the increase in respiratory metabolism after processing did not influence the physicochemical parameters evaluated and T3 obtained the best results in relation to total phenols, PPO activity and IE during the 12 days of storage.